Implementation of literacy program in increasing reading interest and oral language skills of seven-year-old students - Agustina Nua; Elisabet Tantiana Ngura; Dek Ngurah Laba Laksana; Efrida Ita (HAFECS PRESS, 2025)
The purpose of this study is to describe the implementation of the literacy program at UPTD SD Inpres Kolokoa, its implications for reading interest, critical thinking skills, and character formation of students, as well as supporting and inhibiting factors for the implementation of the program. The research approach is qualitative with descriptive research type. Data collection using observation, interview and documentation methods. The literacy program implemented consists of: 1) library visit schedule, 2) making a bulletin board, 3) reading every morning, and 4) reading corner. Data was analyzed by condensing data through the activity of selecting field notes, interview transcripts that were in accordance with the research focus, as well as presenting data by organizing, unifying, and drawing conclusions. Based on the results of the study, it can be concluded that the implementation of the literacy program can increase students' interest in reading and their oral language skills. The implementation of the literacy program at UPTD SD Inpres Kolokoa has a positive influence on the aspects of interest in reading and oral language skills. The increase in students' interest in reading can be seen from students who initially did not like reading books to liking them, even making reading a good habit. Meanwhile, the increase in oral language skills can be seen from several aspects, including students being able to ask questions, share stories, and encourage them to respond. As a result of this literacy program, children's oral language skills have improved, allowing them to retell the stories they have heard to the teacher. Children are able to react to stories told by the teacher. They also develop the ability to recognize vowels and expand their vocabulary through oral games. Abstrak. Tujuan penalitian ini adalan untuk mendeskripisan implementasi program literasi di UPTD SD Inpres Kolokoa, implikasinya terhadap minat baca, kemampuan berpikir kritis, dan pembentukan karakter siswa, serta faktor pendukung dan penghambat berjalanya program. Pendekatan penelitian ini adalah kualitatif denagn jenis penelitian deskriptif. Pengumpulan data menggunakan metode observasi, wawancara dan dokumentasi. Program literasi yang diimplementasikan terdiri dari: 1) jadwal kunjungan perpustakaan, 2) membuat madding, 3) membaca setiap pagi, dan 4) pojok baca. Data dianalisis dengan kondenasi data melalui kegiatan menyeleksi catatan lapangan, transkip wawancara yang sesuai fokus penelitian, serta penyajian data dengan mengorganisasikan, menyatukan, dan menarik kesimpulan. Berdasarkan hasil penelitian dapat disimpulkan bahwa implementasi program literasi dapat meningkatkan minat baca peserta didik serta kemampuan bahasa lisan. Pelaksaan program literasi di UPTD SD Inpres Kolokoa memberikan pengaruh positif dalam aspek minat baca dan kemampuan bahasa lisan. Peningkatan minat baca siswa dapat dilihat dari siswa yang awalnya tidak suka membaca buku jadi menyukainya, bahkan menjadikan membaca sebagai kebiasaan baik. Sedangkan peningkatan kemampuan bahasa lisan dapat dilihat dari beberapa aspek daintaranya siswa dapat mengajukan pertanyaan, berbagi cerita, dan mendorong mereka untuk merespons. Sebagai hasil dari program literasi ini, keterampilan bahasa lisan anak meningkat, sehingga memungkinkan mereka menceritakan kembali cerita yang telah mereka dengar kepada guru. Anak mampu bereaksi terhadap cerita yang disampaikan guru. Mereka juga mengembangkan kemampuan mengenali vokal dan memperluas kosa kata melalui permainan lisan.